The body type profile of women occupying modern pentathlon - Jagiello Wladyslaw; Jagiello Marina; Kozina Zh.L (Kharkov National Pedagogical University, 2012)
It was made an attempt to define the features of the body structure athletes - members of the Polish national team in modern pentathlon (n = 11). Age athletes were in the range of 18-35 years old (23,4 ± 5,2), and training experience - 6-20 years old (12,4 ± 4,4). The five factors (Rohrera, Queteleta II, Manouvrier, height-weight, pelvic and shoulder), and the total body surface were defined. The share based on body measurements of skin-fat folds using prediction equations Piechaczka is calculated. Total fat as a percentage of body weight using the formula Brożka i Keys is calculated. At all were defined 20 indicators. On the basis of the valuation of the body structure specifies a profile of the subjects were determined. A comparison group is consisted of students of Warsaw University of Technology. The members of the women's national team of Poland in modern pentathlon are characterized, above all, significant indicators of the body length of the upper and lower extremities, with a diameter of forearm, elbow width, as well as the value of the proportion of the body.